2021
DOI: 10.1002/sstr.202100029
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Storage in Carbon Cloth–Supported KNb3O8 Nanorods Toward a High‐Performance Lithium‐Ion Capacitor

Abstract: Exploration of novel anodes with a high capacity and fast charge rate is crucial for developing high‐energy‐density lithium‐ion capacitors. Herein, high‐rate Li+ insertion into KNb3O8 nanorods grown on conductive carbon cloth (CC) by a facile electrodeposition technique is reported. The hierarchically porous network and the enhanced conductivity enable the CC‐KNb3O8 electrode to deliver a high discharge capacity of 271 mA h g−1 at 0.01 A g−1 with a low yet safe voltage (1.2 V versus Li/Li+) while exhibiting ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…In the past reports, low-dimensional KNb 3 O 8 materials synthesized via sol-gel or hydrothermal methods were widely applied in photocatalysis and lithium ion battery. [39][40][41][42][43] However, the disordered morphology of thick KNb 3 O 8 nanoflakes synthesized by the above methods cannot be used in micro-nano devices due to incompatibility with semiconductor processing technology. The low crystallinity, numerous oxygen defects, and unavoidable surface contamination of the liquidphase synthesized KNb 3 O 8 nanoflakes also hinder its development in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…In the past reports, low-dimensional KNb 3 O 8 materials synthesized via sol-gel or hydrothermal methods were widely applied in photocatalysis and lithium ion battery. [39][40][41][42][43] However, the disordered morphology of thick KNb 3 O 8 nanoflakes synthesized by the above methods cannot be used in micro-nano devices due to incompatibility with semiconductor processing technology. The low crystallinity, numerous oxygen defects, and unavoidable surface contamination of the liquidphase synthesized KNb 3 O 8 nanoflakes also hinder its development in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The high-resolution XPS of Nb 3d orbital in Figure a shows two asymmetric peaks. The peaks at binding energies of 206.8 and 209.6 eV correspond to the Nb 4+ 3d 5/2 and Nb 4+ 3d 3/2 orbitals, respectively, while the other two weak and broad peaks at 207.6 and 210.4 eV confirm the presence of Nb 5+ 3d 5/2 and Nb 5+ 3d 3/2 , respectively Figure b shows the high-resolution XPS of the Mo 3d orbital.…”
Section: Results and Discussionmentioning
confidence: 93%
“…The peaks at binding energies of 206.8 and 209.6 eV correspond to the Nb 4+ 3d 5/2 and Nb 4+ 3d 3/2 orbitals, respectively, 30 while the other two weak and broad peaks at 207.6 and 210.4 eV confirm the presence of Nb 5+ 3d 5/2 and Nb 5+ 3d 3/2 , respectively. 31 Figure 3b shows the high-resolution XPS of the Mo 3d orbital. The peaks at 231.9 and 235.0 eV correspond to the hexavalent molybdenum for Mo 6+ 3d 5/2 and Mo 6+ 3d 3/2 orbitals, respectively.…”
mentioning
confidence: 99%
“…It has been reported that TNO wrapped by carbon (TNO@C) matched with a carbon fibers (CFs) cathode to assemble CFs//TNO@C LICs, and LICs exhibited a high ED of 110.4 Wh kg –1 at 99.58 W kg –1 , and even at a PD of 5464 W kg –1 , the ED also remained 20 Wh kg –1 . Besides, Sun et al synthesized KNb 3 O 8 NRs grown on the surface of carbon cloth (CC) (CC-KNb 3 O 8 ) by electrodeposition . The CC-KNb 3 O 8 and AC-constructed LICs (i.e., AC-3//CC-KNb 3 O 8 -2.8) exhibited a maximum ED of 69 Wh kg –1 at a PD of 346 W kg –1 , and the capacity retained 88% for 1000 cycles at 2 A g –1 .…”
Section: Applications In Micsmentioning
confidence: 99%